Distinguishing of tumor cell-targeting peptide ligands through a color-encoding microarray. Issue 24 (4th November 2015) - Wang, Zihua; Wang, Weizhi; Geng, Lingling; Hu, Zhiyuan
Abstract : A silicon-based microarray chip was constructed to discover and to distinguish the specific peptide ligands of HER1 and HER2 through a color-encoding strategy. Abstract : A silicon-based microarray system was constructed to discover the affinity peptides and to distinguish the specific peptides from a high throughput library. Using a color-encoding strategy, in situ peptide distinguishing between HER1 ligands and HER2 ligands was achieved. Novel affinity peptide sequences H1P (HER1 ligand) and H2P (HER2 ligand) were determined with nmol affinity.